Analysis of Maspin Expression in Invasive Ductal Carcinoma of the Breast on Stages IIA and IIIB - Hardika, Arif Satria; Fauziah, Dyah (Folia Medica Indonesiana, 2018)
Mammary Serine Protease Inhibitor (maspin) is a tumor suppressor gene, a member of the serine protease inhibitor (serpin) family that works by inhibiting motility of cell movement, invasion and metastasis. Maspin expression is expected to be a prognostic factor as well as a predictive factor in mammary tumors. However, in some recent studies, maspin has a variety of expressions. Although it is known that no maspine appears as an indicator of tumor progression and metastasis, recent study has shown that maspine expression is associated with an aggressive phenotype of breast cancer and with a poor prognosis. Correlations between maspine expression and poor prognosis have also been reported in pancreatic, ovarian, thyroid, bladder and lung cancers. Knowledge of the expression and role of this maspin as well as its relationship with the pathogenesis of breast invasive ductal carcinoma is still small. The aim of this study was to look at differences in maspin expression in breast-invasive ductal carcinoma of stage IIA and stage IIIB groups. This research method used analytic observational research with cross sectional approach. The samples were invasive carcinoma of NST paraffin at the Department of Anatomic Pathology of Dr Soetomo Hospital, Surabaya, from January to December 2015. Thirty samples were divided into two groups, namely stage IIA and stage IIIB groups and immunohistochemical examination with maspin antibody was carried out. The difference of maspin expression in stage IIA and stage IIIB was analyzed using Mann-Whitney statistic test. There were significant differences in maspin expression between stage IIA and stage IIIB groups, where stage IIA has a high maspin expression rather than stage IIIB.